The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review. Issue 29 (17th October 2022) - Vo Van Regnault, G.; Costa, M. C.; Adanić Pajić, A.; Bico, A. P.; Bischofova, S.; Blaznik, U.; Menniti-Ippolito, F.; Pilegaard, K.; Rodrigues, C.; Margaritis, I.
Abstract: According to the European Union regulation, some countries have established a pre-market notification system for food supplements while others have not. As this regulation is unfulfilled, a notified and marketed food supplement ingredient in one country may be forbidden in another. Even though food supplements shall not be placed on the market if unsafe, some products may still expose the consumers to risks. The risk is increased by easier access due to worldwide dissemination fostered by the internet and free movement of goods in the European Union. The Rapid Alert System for Food and Feed and the Emerging Risks Exchange Network are described. To date, the European Union legislation does not include a provision to establish a dedicated vigilance system for food supplements (Nutrivigilance). Six European Union countries have nevertheless set up national systems, which are presented. The present lack of European Union data collection harmonization, does not allow easy cooperation between countries. This article advocates for creating a coordinated European Nutrivigilance System to detect and scrutinize adverse effects of food supplements. This, to help in directing science-based risk assessments and reinforce the science-based decision of policy makers to improve public health safety.